Предмет: Алгебра, автор: mumiamakaka

ДАЮ МНОГО БАЛЛОВ
ТОЛЬКО 1пример, производные по определению

Приложения:

Ответы

Автор ответа: NNNLLL54
0

y(x)=\frac{x}{2}-x^2\\\\\Delta y=y(x_0+\Delta x)-y(x_0)=\frac{x_0+\Delta x}{2}-(x_0+\Delta x)^2-(\frac{x_0}{2} -x_0^2)=\\\\=\frac{x_0}{2}+\frac{\Delta x}{2}-x_0^2-2x_0\cdot \Delta x+(\Delta x)^2-\frac{x_0}{2}+x_0^2=\frac{\Delta x}{2}-2x_0\cdot \Delta x+(\Delta x)^2\\\\\\\lim\limits _{\Delta x \to 0}\dfrac{\Delta y}{\Delta x}=\lim\limits _{\Delta x \to 0}\dfrac{\frac{\Delta x}{2}-2x_0\cdot \Delta x+(\Delta x)^2}{\Delta x}=\lim\limits _{\Delta x \to 0}(\frac{1}{2}-2x_0+\Delta x)=\\\\\\=\frac{1}{2}-2x_0

\Rightarrow \; \; \; \; \boxed {\; y'(x)=\frac{1}{2}-2x\; }

Похожие вопросы